Atypical strains of Toxoplasma gondii and its impact on development of toxoplasmosis (Research, Society and Development, 2023)
This article aims to clarify the population structure of T. gondii strains, their virulence patterns, and the characterization of atypical strains addressing changes and complications related to T. gondii strains. Fifty-nine references in Portuguese, English, and Spanish from 1992 to 2021 were selected from the research bases PubMed, SciELO, Elsevier, ScienceDirect, and Google Scholar, using the keywords Toxoplasma gondii, Genotyping, and toxoplasmosis alone or in a combined form. T. gondii has a life cycle with well-defined sexual reproduction that occurs in nature more rarely in countries of North America and Europe. Based on strains isolated in these regions, the population of T. gondii was differentiated into three clonal lineages, implying a low genetic diversity. Despite the observed genotypic pattern, South America, especially Brazil, has shown the existence of a higher genetic variability, characterizing non-clonal genotype strains called atypical. The presence of these strains may be associated with the wide geographic distribution, fauna, and recombination of clonal strains through the sexual cycle in the feline. The correlation between the virulence of the Brazilian strains and the symptoms presented by patients with toxoplasmosis is not well-defined yet. However, these patients show a greater severity of the disease compared to infections in European and North American countries, pointing to a possible relationship between the genetic polymorphism of T. gondii strains with the pathogenesis of toxoplasmosis.